Factors that Generate Nonconformities in the Electrostatic Powder Painting. (2015) - Jozsef, Boer; Blaga, Petruţa
Abstract: A product, a process or service is considered nonconforming when one or more of its characteristics do not meet the specified requirements. Nonconformities may result from deficiencies in the internal management of the organization, due to internal or external complaints or due to dissatisfaction with the specific requirements of the product or service. The department of quality can analyse reported nonconformities with special instruments, it finds generating factors of nonconformities and suggests solutions in order to prevent and rectify the identified nonconformities, to improve the performances of the organization.